2015
DOI: 10.1590/0037-8682-0222-2014
|View full text |Cite
|
Sign up to set email alerts
|

Using the International Classification of Functioning, Disability and Health as a tool for analysis of the effect of physical therapy on spasticity in HAM/TSP patients

Abstract: Introduction:This study aimed to evaluate spasticity in human T-lymphotropic virus type 1-associated myelopathy/tropical spastic paraparesis (HAM/TSP) patients before and after physical therapy using the International Classifi cation of Functioning, Disability and Health (ICF). Methods: Nine subjects underwent physical therapy. Spasticity was evaluated using the Modifi ed Ashworth Scale. The obtained scores were converted into ICF body functions scores. Results: The majority of subjects had a high degree of sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…Based on the observational studies, it is confirmed that the main problems that affect these patients involve disorders of gait 21,22,8,23 , balance 24,25,26 , pelvic floor 27,28 spasticity 29,30 and pain 10,31,32,33 . These dysfunctions affect daily life activities 5,34 and quality of life 35 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Based on the observational studies, it is confirmed that the main problems that affect these patients involve disorders of gait 21,22,8,23 , balance 24,25,26 , pelvic floor 27,28 spasticity 29,30 and pain 10,31,32,33 . These dysfunctions affect daily life activities 5,34 and quality of life 35 .…”
Section: Discussionmentioning
confidence: 93%
“…Two studies of diagnostic accuracy were found. One addressed the use of the International Classification of Functioning (ICF) 30 and the other the use of methods to assess biomechanics and postural control in this population 50 . The more accurate the diagnosis, the greater the possibility that research will detect the differences obtained by an intervention and the greater certainty about its effectiveness for clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 11 studies extracted, 1 was a quasi-experimental study,[ 16 ] 5 were a randomized clinical trial,[ 14 17 18 19 20 ] and 5 were a randomized crossover clinical trial. [ 11 12 13 15 21 ] Furthermore, 18/18% of articles (2 cases) were of low quality[ 16 17 ] and 81/81% of articles (9 cases) were of high quality[ 11 12 13 14 15 18 19 20 21 ] [ Table 2 ].…”
Section: Resultsmentioning
confidence: 99%
“…In these studies, the main intervention approaches are physiotherapy, which includes exercise therapy,[ 11 19 20 ] specialized physiotherapy movement,[ 12 16 18 ] and electrotherapy. [ 14 ] One study also used combination interventions in the form of behavioral therapy, physical exercise, and electrotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…6,10,15,16 Estas incapacidades físicas alteram diretamente a funcionalidade dos pacientes com PET/MAH, assim estudos têm mostrado que o uso da Classificação Internacional de Funcionalidade, Incapacidade e Saúde (CIF) fornece base científica para maior compreensão do estado de saúde do indivíduo, bem como para a comunicação unificada entre profissionais de saúde e pesquisadores. 17,18 Deste modo, a Organização Mundial da Saúde (OMS) desenvolveu a CIF para fornecer uma estrutura multidimensional e linguagem padrão para a descrição de componentes relacionados à saúde e bemestar. A CIF tem se tornado importante classificação de funcionalidade e incapacidade, permitindo visão cada vez mais global e abordagem positiva para o estado clínico do indivíduo.…”
unclassified